Long-term effects of mindfulness-based cognitive therapy in patients with obsessive-compulsive disorder and residual symptoms after cognitive behavioral therapy: Twelve-month follow-up of a randomized controlled trial. (September 2020) - Cludius, Barbara; Landmann, Sarah; Rose, Nina; Heidenreich, Thomas; Hottenrott, Birgit; Schröder, Johanna; Jelinek, Lena; Voderholzer, Ulrich; Külz, Anne Katrin; Moritz, Steffen
Highlights: MBCT was tested as an intervention in patients with OCD who had not sufficiently profited from previous cognitive-behavior therapy. MBCT was not more effective than a psychoeducation group in OCD at a 12-months follow-up. Exploratory analyses revealed superiority of MBCT on some aspects of OCD. Abstract: We examined the long-term efficacy of mindfulness-based cognitive therapy (MBCT) compared to a psychoeducation group as an active control condition in patients with obsessive-compulsive disorder (OCD) with residual symptoms of OCD after cognitive behavioral therapy. A total of 125 patients were included in a bicentric, interviewer-blind, randomized, and actively controlled trial and were assigned to either an MBCT group ( n = 61) or a psychoeducation group ( n = 64). Patients' demographic characteristics and the results from our previous assessments have already been reported (Külz et al., 2019). At the 12-month follow-up the completion rate was 80%. OCD symptoms were reduced from baseline to follow-up assessment with a large effect, but no difference was found between groups. Exploratory analyses showed that a composite score of time occupied by obsessive thoughts, distress associated with obsessive thoughts, and interference due to obsessive thoughts differed between groups in the per-protocol analysis, with a stronger reduction in the MBCT group. At the 12-month follow-up, the two groups showed a similar reduction of symptoms. However, preliminary evidence indicates that MBCT has a superior effect on some aspects of OCD. This should be replicated in future studies.